2009
DOI: 10.4141/cjps07162
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analyses of genetic variation of Eupatorium adenophorum (Asteraceae) populations in China

Abstract: . 2009. AFLP analyses of genetic variation of Eupatorium adenophorum (Asteraceae) populations in China. Can. J. Plant Sci. 89: 119Á126. The Eupatorium adenophorum is one of the most widespread invasive alien species in China. In the present study, the genetic variation and population structure of this species were analyzed using amplified fragment length polymorphism (AFLP) markers. Nine primer pairs were selected for the analysis and 685 bands were produced, among which 474 bands were polymorphic (PPB 069.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The abundance of tamarisk hybrids in North America compared to the lack of interspecific hybridization in the native range in Asia suggests that species introgression has played an important role for invasion success (Gaskin and Kazmer 2009;Gaskin et al 2012). Similar patterns of latitude and genetic variation are demonstrated by at least one other invasive shrub, Eupatorium adenophorum (Huang et al 2009).…”
Section: Discussionmentioning
confidence: 89%
“…The abundance of tamarisk hybrids in North America compared to the lack of interspecific hybridization in the native range in Asia suggests that species introgression has played an important role for invasion success (Gaskin and Kazmer 2009;Gaskin et al 2012). Similar patterns of latitude and genetic variation are demonstrated by at least one other invasive shrub, Eupatorium adenophorum (Huang et al 2009).…”
Section: Discussionmentioning
confidence: 89%
“…From there, the populations in western Yunnan spread northward to southern Sichuan, and further dispersed to the Yangtze River valley in Sichuan by water flow. Several southeastern populations spread eastward to northwestern Guangxi Province, and others spread northward to the central part of Yunnan and northeastward to the western part of Guizhou Province [20,14,[17][18][19]. The ISSR-PCR analysis with the individuals/populations of A. adenophora detected intra-specific polymorphism of nuclear DNA, however, the PCR-RFLP analysis of 256 individuals revealed no variations in cDNA in the Chinese populations.…”
Section: Genetic Variation and Evolutionary Mechanism Of A Adenophoramentioning
confidence: 93%
“…The results showed that it has many geographical populations in China, and genetic differentiations occurred within those populations. Inter-simple sequence repeat (ISSR) markers were used to assess the bio-geographic relationships among 64 populations of A. adenophora during 2004-2006 in China and Neighbor-joining (NJ) cluster analysis based on genetic distances among the populations grouped the populations according to their geographical origin, i.e., populations of Southwestern Guizhou, populations of Liangshan city in Sichuan, populations of Western Guizhou, populations of Guangxi plus Chongqing, populations of Southern Yunnan, and populations of Yangtze River Valleys in Sichuan plus western Yunnan , environmental isolation is the primary reason of for the genetic differentiation of the alien species [13][14][15][16][17][18][19].…”
Section: Genetic Variation and Evolutionary Mechanism Of A Adenophoramentioning
confidence: 99%
“…Research carried out by using intersimple sequence repeat (ISSR) markers and amplified fragment length polymorphism (AFLP) method in China exhibited genetic variations in the population of A. adenophora (Gui et al ., ; Huang et al ., ). This genetic diversity or genetic distance increased with increasing geographic distance and elevation (Gui et al ., ; Huang et al ., ). More genetic heterogeneity within populations of A. adenophora explains the possibility of multiple introduction in China (Huang et al ., ).…”
Section: Biology Of Ageratina Adenophoramentioning
confidence: 97%